Management of newly diagnosed diabetes: home or hospital?. Issue 10 (21st September 2004) - Lowes, L; Gregory, J W
Abstract : Type 1 diabetes is one of the most common chronic childhood disorders, occurring with increasing frequency. Diabetes management involves the child and family learning how to inject insulin and monitor blood glucose, and adhere to a diet containing healthy food choices. Medical interventions necessary to stabilise newly diagnosed diabetes depend upon the clinical condition of the child at presentation. Hospital admission is necessary if intravenous therapy is required to correct dehydration, electrolyte imbalance, and ketoacidosis, with progression to oral fluids and subcutaneous insulin administration as the child's condition improves. If the child is mildly to moderately symptomatic and clinically well, subcutaneous insulin and oral diet and fluids may be begun from the time of diagnosis, and stabilisation at diagnosis does not necessarily require hospital admission. This article reviews the evidence concerning hospital or home based treatment at diagnosis for children with type 1 diabetes. The Cardiff approach to home management is briefly described, and the benefits and disadvantages of different approaches to initial management are discussed.